Studies on the section Lactifluus, of the genus Lactarius in India - and R.D. GAUR, V.K. BHATT, R.P. BHATT* (Indian Phytopathology, 2002)
The three species belonging to section Lactifluus of the genus Lactarius; Lactarius corrugis, L. hygrophoroides with its type species and three varieties (var. lavendulaceus, var. odoratus and var. rugatus), L. volemus with its type species and variety flavus, are described and illustrated. Out of these, all the three variants of Lactarius hygrophoroides are new to India although the morphological and anatomical details of L. volemus var. flavus from India are presented for the first time. A dichotomous key is also given for all the seven taxa. The distribution of these species in 3 forest ecosystems in relation to ecological parameters, including mycorrhizal associations and growth habit, are also discussed.